2016
DOI: 10.1504/ijcistudies.2016.077131
|View full text |Cite
|
Sign up to set email alerts
|

Integration of knowledge management systems and business processes using multi-agent systems

Abstract: Applications of agents in supporting an organisation's operations addressed in academic literature largely refer to issues connected with business processes and management of an organisation knowledge, which are considered separately. In the first case, multi-agent systems are perceived as an element that performs and automates business processes of an organisation and substitutes its IT systems and users. In the second case, agent solutions are perceived as tools designed to automate or support the user in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The proposed methodology has been developed upon the experience regarding the developed prototype of agentbased solutions supporting the operation of the organization and developed in the context of building solutions supporting the interaction of users within the business processes in which they participate [12].…”
Section: Methodological Aspects Of the Software Agents' Societiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed methodology has been developed upon the experience regarding the developed prototype of agentbased solutions supporting the operation of the organization and developed in the context of building solutions supporting the interaction of users within the business processes in which they participate [12].…”
Section: Methodological Aspects Of the Software Agents' Societiesmentioning
confidence: 99%
“…Depicted in the [12] prototype of agents' society was used to evaluate elements of the methodology and pointed to possible applications of agents' society to assist the interaction processes between users.…”
Section: Methodological Aspects Of the Software Agents' Societiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Agent-based chatbots can push the interactions and capabilities far beyond the conventional (mainly procedural/static) interactions characterizing chatbot employed in a plethora of application domains (i.e., retail [32], tourism [33], etc.) For example,Żytniewski [34] studied agent-based chatbots as a bridge between users and IT systems in business processes and management of the organization knowledge. Alencar and Netto [35] proposed an approach to improve the cooperation among students and learning institutions.…”
Section: Multi-agent Systems and Chatbotsmentioning
confidence: 99%
“…The author's earlier research [8], [9], [10], [11] has shown that the theory of software agent societies and its use in knowledge-based organisations requires a separate view of the characteristics of multi-agent systems. Especially in the area of the application of methods for knowledge representation in such systems and possibilities of using autopoietic solutions to support the different stages of the life cycle of the process of knowledge management [8], [12].…”
Section: Introductionmentioning
confidence: 99%